The Effects of Harvesting Heights at Different Stubble Heights on Forage Yield and Quality in Sorghum Sudangrass Hybrid Cultivars - Nuri Erecek; Ahmet Gökkuş; Fırat Alatürk (Acta Natura et Scientia)
This study was carried out to determine the forage yield and quality of three sorghum sudangrass hybrid cultivars (Greengo, Hay Buster BMR and Cattleman’s Choice) harvested at different stubble heights (5, 10, and 15 cm). The research was conducted in Kalafat village of Çanakkale Province during 2019 and 2020. The experiment was established using a randomized complete block design with 3 replications. Cultivar and stubble heights were considered as two different factors. Crude protein, neutral detergent fiber (NDF), acid detergent fiber (ADF), and digestible dry matter ratios along with the yields of hay and crude protein determined in this study. The hay yield of sorghum cultivars decreased depending on the increase in remaining stubble heights. The crude protein ratio showed a difference only in terms of cultivars, but crude protein yield differed significantly only according to stubble heights. NDF and ADF ratios along with the digestible dry matter ratios changed significantly only between the years. According to the overall results of this study, the Cattleman’s Choice cultivar and the cutting height of 5 cm could be recommended in sorghum × sudangrass hybrid cultivation for roughage production in summer under ecological conditions similar to Çanakkale province.